THE BIBLE’S VIEWPOINT OF THE COMMUNICATION OF ENGLISH LANGUAGE CLASSES - Jo’raeva Zulayho Shamshidinovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides recommendations for developing communication relationships using traditional methods in English courses. Several methods are also given as examples.